Bilateral Mooren’s Ulcer - Uday Gajiwala; Jyotsom Ganatra; Rajesh Patel; Parin Shah; Rohan Chariwala (Delhi Journal of Ophthalmology)
Mooren’s Ulcer is an idiopathic, rapidly progressive, painful peripheral ulcerative keratitis with no associated scleritis. It’s a diagnosis of exclusion which means all other diagnosable systemic disorders that could be responsible for the progressive destruction of cornea must be ruled out. The etiology of Mooren’s Ulcer remains uncertain. However, recent studies indicate that it is an autoimmune disease directed against a specific target molecule in the corneal stroma, triggered in genetically susceptible individuals by one of several possible mechanisms.